Fixture Design for Outer Skin Aircraft Door Manual Drilling Operation with Finite Element Analysis and Ergonomic Consideration - Azuddin Mamat; Hwa Jen Yap; Chee Hau Tan; Muhammad Basril Muhammad Asri (Advances in Materials Science and Engineering, 2022)
Fixture design for dedicated aircraft components is very challenging nowadays due to complexity, process capability, and effect on technical worker health conditions. The proposed fixture design for drilling an outer skin aircraft door will accommodate a design principle of fixture and ergonomic aspect of the technical worker. The proposed design will include the comfort drilling posture and finite element analysis (FEA) on the structure. The step required for the drilling process, starting from loading, locating, clamping, frame rotation, and hole drilling was discussed. FEA analysis shows a maximum value for the von Mises stress recorded was 6.373 × 105 N/m2 at the flange between the frame and vertical stand, and acceptable stress distribution results from the loaded weight of the outer skin aircraft door. A fully functional prototype was developed with a scale reduced to a quarter to verify the design. The developed prototype is successfully showing the capability of the fixture design in providing a mechanism of ergonomic consideration in the drilling of the outer skin of the aircraft door.